MEMÓRIA E IDENTIDADE DE UM BAIRRO: CAMPINAS SOB AS LENTES DE HÉLIO DE OLIVEIRA - TITO, Keith Valéria (2008)
The use of the photos combined to oral reports recover the historical trajectory of specific social groups. From photographs of Campinas produced by the photographer Hélio de Oliveira and the combination of these with the oral documentation, it is considered the forms of construction over the years, the feeling of belonging, training and consolidation of the identity of the residents of Campinas, municipality that, in mid-1930, has been incorporated to Goiânia, capital of the new State of Goiás, coming to be one of the neighborhoods in the subsequent decades. Key-words: Campinas, Goiânia, photographs, memory, identity, soccer, goianiense athletic club, Hélio de Oliveira.